Key technologies of personnel location’s management system for pumped storage power station - Na MA; Li JIN (Dianxin kexue)
The ultra wideband location has the advantages of low power consumption,high speed transmission and high security level,especially it can support high location accuracy.It plays an irreplaceable role in the information construction of pumped storage power station.The ultra wideband positioning technology was introduced.The positioning technologies such as RFID,ZigBee,high-frequency pulse were compared and analyzed.The system architecture and positioning principle were described.Finally,the application of the pumped storage power station were introduced.